Haptic and Audio Interaction Design 7th International Conference, HAID 2012, Lund, Sweden, August 23-24, 2012. Proceedings - Magnusson, Charlotte; Szymczak, Delphine; Brewster, Stephen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 7th International Conference on Haptic and Audio Interaction Design, HAID 2012, held in Lund, Sweden, in August 2012. The 15 full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on haptics and audio in navigation, supporting experiences and activities, object and interface, test and evaluation.
haptics and audio in navigation -- supporting experiences and activities -- object and interface -- test and evaluation.
Keywords: Computer science; Multimedia systems; Education; Computer Science; User Interfaces and Human Computer Interaction; Media Design; Multimedia Information Systems; Computers and Society; Models and Principles; Computers and Education